2019
DOI: 10.1212/nxi.0000000000000535
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory myopathy with myasthenia gravis

Abstract: ObjectiveTo provide evidence that idiopathic inflammatory myopathy (IM) with myasthenia gravis (MG) frequently shows thymoma association and polymyositis (PM) pathology and shares clinicopathologic characteristics with IM induced by immune checkpoint inhibitors (ICIs).MethodsWe analyzed the clinicopathologic features of 10 patients with idiopathic IM and MG identified in 970 consecutive patients with biopsy-proven IM.ResultsSeven patients (70%) had thymoma. IM and MG were diagnosed with more than 5-year time d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…On the hand, concomitant myositis or myocarditis is rarely observed in idiopathic MG and is usually reported in cases of thymoma-associated MG [31,32]. Interestingly, we detected anti-titin antibodies in three out of four patients with MG/myositis/myocarditis (75%), confirming previous reports [33,34].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the hand, concomitant myositis or myocarditis is rarely observed in idiopathic MG and is usually reported in cases of thymoma-associated MG [31,32]. Interestingly, we detected anti-titin antibodies in three out of four patients with MG/myositis/myocarditis (75%), confirming previous reports [33,34].…”
Section: Discussionsupporting
confidence: 89%
“…The co-occurrence of myocarditis [ 28 ] and the elevation of serum troponin [ 29 ] have been identified as predictors of poor prognosis in patients with ir-MG/myositis and IM3OS is characterized by a high mortality (up to 60% of cases) [ 30 ], which can occur due to both cardiac (i.e., arrythmia) and neuromuscular (i.e., respiratory failure) involvement. On the other hand, concomitant myositis or myocarditis is rarely observed in idiopathic MG and is usually reported in cases of thymoma-associated MG [ 31 , 32 ]. Interestingly, we detected anti-titin antibodies in three out of four patients with MG/myositis/myocarditis (75%), confirming previous reports [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al demonstrated that the prevalence of inflammatory myopathies in a cohort of 924 MG patients was 0.9% (8/924) [ 16 ]. Similar co-existing diagnoses were reported in an analysis of 970 confirmed IIM patients, where Uchio and colleagues found that the prevalence of concomitant MG was 1.03% (10/970) [ 40 ]. The clinicopathologic features of these 10 patients were comparable to those in our literature review.…”
Section: Discussionsupporting
confidence: 77%
“…In cases where the initial diagnosis was MG, patients presented with typical MG symptoms, followed by myopathy, with a predominant association with polymyositis [11,12]. Thymoma has been associated with rhabdomyolysis-like features, respiratory failure, and dropped head; however, cardiac involvement and ocular symptoms are more commonly observed [13]. Nonetheless, the association between MG and IIM without thymic pathology occurs in 45% of cases [14,15].…”
Section: Discussionmentioning
confidence: 99%